Critical Water Effect on the Plasmon Band and Visible Light Activity of Au/ZnO Nanocomposites - Aguirre, Matias E.; Gusto, G.; Goes, Marcio S. [UNESP]; Bueno, Paulo Roberto [UNESP]; Zampieri, G.; Grela, Maria A. (Amer Chemical Soc, 2014)
Small amounts of water (between and 0.05 and 0.35% V/V) critically determine the morphology and plasmon band of Au/ZnO nanostructures obtained by Au3+ photoreduction on ZnO nanoparticles dispersed in 2-propanol. All the synthesized materials exhibit plasmon induced activity to drive the solvent oxidation; however, the temporal evolution of acetone shows a clear induction time followed by the sudden boost in the rate of the oxidation product, which depends on the photodeposition conditions. Xray photoelectron spectroscopy (XPS) indicates that visible irradiation produces the transformation of surface Au(0) in Au(+). Besides, an increment in the ZnO surface area ascribed to the photoinduced fragmentation of aggregated networks of Au/ZnO nanocomposites is evidenced by XPS and simple adsorption experiments. The changes in the surface properties correlate with the onset in the catalytic activity. Possible mechanisms are discussed to account for the experimental findings.